Strategies to Strengthen Understanding of Science Concepts - DOGRA, BHARTI (THE PRIMARY TEACHER, 2015)
Science teachers use a variety of strategies for supporting learning of diverse students. These strategies can be used during different stages of planning a lesson plan — before teaching to get an idea about their previous knowledge, to prepare them for the lesson, during the lesson and for assessing their learning. These strategies can help in scaffolding learning of the students. The selection of the strategies can be done keeping in mind nature of the topic, learning needs and learning styles of students.